OBTAINING THE RECOMBINANT IMMUNOGENIC DOMAIN OF THE RABIES VIRUS NUCLEOPROTEIN - Tursunov , K.; Begaliyeva , A.; Inirbay , B.; Mukanov , K.К.; Ramanculov , Е.М.; Shustov , А.В.; Mukantayev , K.N. (Eurasian Journal of Applied Biotechnology, 2015)
Rabies is an important concern in the Republic of Kazakhstan due to its widespread incidence in the country. The main sources of the disease in the Republic are natural, such as viral transmission through populations of wild carnivores and rodents, and anthropurgic, such as viral transmission through populations of domesticated animals. The ability of rabies virus to spread rapidly underscores the importance of developing diagnostic measures during both prevention and quarantine efforts as these could be used to quell emerging out breaks. With the increase in the rate of diagnostic method development, problems have arisen with the inconsistency of antigens and antibodies used to develop diagnostic test systems. The rabies virus nucleoprotein (N protein) is an important target for the immunochemical diagnosis of rabies. Thus, we created a genetic construct based on plasmid pET32 that expresses the С-terminal fragment of the rabies virus nucleoprotein. Our genetic construct was transformed into E. coli competent cells and the parameters of isolation and purification of the recombinant rabies virus nucleoprotein were optimized. We found that the fragment with the most immunogenic site on the nucleoprotein was located at position 360–389 amino acids. The molecular weight of the recombinant antigen was 42 kDa. The serum from mice immunized with fixed rabies virus reacted specifically with this recombinant C-terminal fragment of the nucleoprotein virus. The serum from mice immunized with recombinant antigen and fixed virus showed cross-reactivity at high dilution titers.